Consensual Assessment of Creativity in Teaching Design by Supportive Peers—Its Validity, Practicality, and Benefit. (28th November 2015) - Cheng, Vivian M. Y.
Abstract: Creativity in teaching is a significant and complex construct. However, in the local educational context, creativity in teaching has received little attention. This study aimed to investigate the validity, practicality, and benefits of applying a modified consensual assessment technique (CAT) to assess creativity in teaching design. Four hundred and eighty‐five written teaching designs were collected from 167 in‐service and pre‐service primary school teachers in Hong Kong. Instead of expert teachers, "supportive" peers, who had shown support, interest, and initiative in creative teaching were recruited as judges. A warm‐up exercise, with no definition of creativity, was given to the judges before beginning their assessments. The results indicated overall consistency in the judges' assessments of creativity, and that creativity factor could be distinguished from pedagogical skills and other technical factors. Most of the peer judges reported personal gains in creative teaching by engaging in the assessment process. On average, each judge spent approximately only 2 minutes rating each written teaching design. The findings confirm that the modified CAT is a valid and economical assessment method with learning benefits for the judges. The special values and implications of using supportive peer judges in consensual assessment are further discussed.